A Comparative Study Between Time History Analysis and Theoretical Analysis of a Multi-Storey Building in Seismic Zone ? and ? - Mrs. D. Sathiyasree; A. M. Ashwin Kumar; M. Y. Faizail Ahamed; M. Gautham; C. Thamizharasan (International Journal of Scientific Research in Civil Engineering, 2022)
The fact that the earthquake happened in a multistory building demonstrates that if the buildings are not carefully built and constructed with enough strength, they will completely collapse. To maintain the safety of multi-story buildings against seismic forces, seismic analysis must be studied in order to develop earthquake-resistant structures. Response reduction was evaluated in seismic analysis for two cases: ordinary moment resisting frame and special moment resisting frame. The major goal of this research is to look at structural seismic analysis for static and dynamic analysis in both ordinary and special moment resistant frames. In structural seismic analysis, the approaches employed are equivalent static analysis and time history analysis. For the seismic study, we used a residential building with a G+ 9-story construction that is situated in zone I. ETABS software was used to examine the whole structure on a computer. In static and dynamic analysis, we observed the response reduction of instances ordinary moment resisting frame and special moment resisting frame values using deflection diagrams. The resisting frame structure's unique moment is effective in resisting seismic stresses. Static and dynamic analyses are compared, and data such as bending moment, nodal displacements, and mode shapes are observed, compared, and presented. The base shear performance of the building is investigated in all of the situations stated, and the findings show the relevance of variation in these parameters in a structure's reaction to lateral loading. ETABS is used to do reaction spectrum analysis and time-history analysis, with the findings of the study being confirmed.
Keywords: Equivalent Static Analysis; Time History Analysis; ETABS Software; Displacement